2018
DOI: 10.5688/ajpe6150
|View full text |Cite
|
Sign up to set email alerts
|

Review of Grit and Resilience Literature within Health Professions Education

Abstract: Objective. To review literature pertaining to grit and resilience in health professions education. Findings. There is significant interest in grit and resilience throughout the health professions, but little has been published with regard to pharmacy. Although there are methodological issues with defining and measuring grit and resilience, several studies have shown relationships between the constructs and personal and academic well-being. Educational interventions aimed at increasing grit and resilience have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
142
0
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 182 publications
(158 citation statements)
references
References 65 publications
8
142
0
8
Order By: Relevance
“…Interestingly, students in other health professional courses had similar mean levels of grittiness (medical, 4.01 ± 0.4; pharmacy, 3.7 ± 0.5; occupational therapy, 3.78 ± 0.46; nursing, 3.27 ± 0.58) . Conversely, lower proportions of medical students have low resilience (13%) compared with the physiotherapy students in this study (25%) .…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…Interestingly, students in other health professional courses had similar mean levels of grittiness (medical, 4.01 ± 0.4; pharmacy, 3.7 ± 0.5; occupational therapy, 3.78 ± 0.46; nursing, 3.27 ± 0.58) . Conversely, lower proportions of medical students have low resilience (13%) compared with the physiotherapy students in this study (25%) .…”
Section: Discussionmentioning
confidence: 47%
“…Resilience was assessed using the Brief Resilience Scale (BRS) and Academic Resilience Scale (ARS) (Table ) . Grit was assessed using Grit‐S and mindset type was assessed via the Dweck Mindset Instrument (DMI) (Table ) …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, gritty adult learners reach higher educational achievements, and gritty teachers are more likely to retain their jobs and instill higher academic performance in students . Grit and resilience have also been offered as a possible explanations for success in health professional students who succeed in the face of pressure …”
mentioning
confidence: 99%
“…5 Grit has been the subject of a few investigations of students in health professions. 6 Among 702 pharmacy students, grit was a signifi cant and independent predictor of academic performance. 7 In a study of undergraduate nursing students, researchers found statistically signifi cant positive associations between grit and both course engagement and skill development.…”
mentioning
confidence: 99%